KELUARGA SEBAGAI GARDA TERDEPAN PERLINDUNGAN ANAK - Elvi Hadriany (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2017)
Children are the greatest assets of parents, and therefore must be educated as well as possible so that later they can be people who can provide happiness to parents. Educating children is a long process that must be considered by parents in accordance with the level of development. The family as the first and foremost educational tool for children must be able to create an atmosphere and educational process for children based on the child's developmental tasks and the needs of the times while still emphasizing the values of intelligent characters.Keywords: Family, child protection, guard